INVESTIGATION OF MIDDLE-SCHOOL STUDENTS' VOCABULARY MASTERY BY USING SPIDER WORD WEBBING - Amiruddin; Razaq, Yusuf; Satriani; Natasya, Nurul (SOKO GURU: Jurnal Ilmu Pendidikan, 2021)
The goal of this study was to determine whether or not using the Spider Word Webbing approach could increase students' vocabulary proficiency in terms of form, meaning, and use. The researcher used a pre-experimental design. The sample for this study was 25 students in their second year of Middle School (MTs Muhajirin As'adiyah Kampiri in the academic year 2019/2020) drawn from a population of 95 students using purposive sampling. A vocabulary test was provided before and after treatment to determine the pupils' language mastery. This study found that using the Spider Word Webbing approach increased students' vocabulary mastery at MTs Muhajirin As'adiyah Kampiri. The t-test (9.050) has a higher value than the t-table (2.064), and the degree of freedom (df) is 24. The null hypothesis (H0) is rejected, while the alternative hypothesis (H1) is accepted. The Spider Word Webbing approach is found to be successful in improving students' vocabulary mastery in terms of form, meaning, and use.